Smart city data commons and EU competition law: A conflict in the making? - Aleksi Kajander; Thomas Hoffmann (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
Open data has been heralded as bringing great benefits to businesses and individuals alike in the EU, enabling the emergence of a data agile Europe and a society empowered by data. However, such arrangements are far from being free of disadvantages, especially for the citizens of smart cities. If the data generated by smart cities is made open almost by default, there is a serious risk of data disenfranchisement for the smart citizens, who may be negatively impacted by the publication of even non-personal smart city data. Consequently, Ostrom's commons have been considered as a possibility to re-empower smart citizens in regard to their data through self-governance. However, should smart citizens decide to make data available only to select users, they could potentially run into a conflict with EU competition law. Potential sources of conflict include violations of Articles 101 and 102 of the TFEU, through decisions made in the context of the self-governing smart city data commons. Consequently, this paper seeks to identify the potential conflicts between managing non-personal smart city data as a commons and EU competition law.
Keywords: K21; L86; 034; R38; D86; H83; 330; Smart city; Data; Commons; Ostrom; Competition law; European Union